'YOURS TO HAND, AND THE FOLLOWING IS THE INFORMATION YOU REQUIRE . . .': LETTERS TO THE EDITOR IN THE JAMES CATTON ARCHIVE AT ARSENAL FOOTBALL CLUB MUSEUM AND THE PRACTICALITIES OF WRITING THE NEWS ON THE EARLY TWENTIETH-CENTURY SPORTING PRESS. Issue 130 (April 2015) - Steve, Tate
Abstract : This paper considers the collection of correspondence and ephemera associated with the career of sports reporter James Catton, which is held by Arsenal Football Club Museum in London. The Catton material, including items dating from the 1880s to the 1930s, is examined in terms of the potential insight it can provide into the working practices of a successful sports journalist, in particular in the writing of news, in the development of a network of contacts and informants and in the business of knowledge management. The increasing digitisation of Victorian and early twentieth-century newspapers is making the press an ever-more accessible archive for the historian engaged in research, although the journalists who wrote the news often remain at best anonymous within, and more often absent from, the process. The paper considers the opportunity presented by the Catton material to add substance and historicity to the often-elusive figure of the nineteenth- and early twentieth-century reporter. The cuttings and correspondence volumes held by Arsenal FC reveal much about James Catton's work regime and, given his central place in sports journalism in the decades spanning 1900, they in turn throw more light on the world of professional sport, the development of a popular press and the history of journalism.